Review: Evaluasi Fisik terhadap Penggunaan Tepung Komposit pada Kualitas Cookies - Destiana Adinda Putri (Food Scientia : Journal of Food Science and Technology, 2023)
Composite flour is mixture of flour made from tubers, cereals, legumes, and other vegetable base ingredients with or without the addition of wheat flour. The use of various composite flour types in cookies manufacturing is able to reduce the use of wheat flour, provide uniqueness, increase nutritional values, and change physical qualities. The aim of this review is to provide information regarding to the use of composite flour in cookies manufacturing and its effect on physical quality based on several recent studies that was observed. Several studies have shown that the use of composite flour in cookies production results in the changes of physical quality related to weight, weight loss, baking yield, diameter, thickness, spread ratio, color (L*, a*, b*, C*, ΔE, whiteness index, browning index), and texture (hardness, fracturability, cohesiveness, springiness, chewiness, resilience, gumminess). These physical quality changes contribute to different results depending on the type of composite mixture and the percentage of wheat flour or the non-wheat flours. The different nutritional contents also contribute to the physical quality changes of cookies.